Chimeric antigen receptor-T cell therapy-related cardiotoxicity in adults and children cancer patients: A clinical appraisal - Camilli, Massimiliano; Maggio, Luca; Tinti, Lorenzo; Lamendola, Priscilla; Lanza, Gaetano Antonio; Crea, Filippo; Lombardo, Antonella (Frontiers in Cardiovascular Medicine, 2023)
Chimeric antigen receptor-T (CAR-T) cells therapies represents an innovative immunological treatment for patients suffering from advanced and refractory onco-hematological maligancies. The infusion of engineered T-cells, exposing chimeric receptors on the cell surface, leads to an immune response against the tumour cells. However, data from clinical trials and observational studies showed the occurrence of a constellation of adverse events related to CAR-T cells infusion, ranging from mild effects to life-threatening organ-specific complications. In particular, CAR-T cell-related cardiovascular toxicities represent an emerging group of adverse events observed in these patients, correlated with increased morbidity and mortality. Mechanisms involved are still under investigation, although the aberrant inflammatory activation observed in cytokine release syndrome (CRS) seems to play a pivotal role. The most frequently reported cardiac events, observed both in adults and in the pediatric population, are represented by hypotension, arrhythmias and left ventricular systolic dysfunction, sometimes associated with overt heart failure manifestations. Therefore, there is an increasing need to understand the pathophysiological basis of cardiotocixity and risk factors related to its development, in order to identify most vulnerable patients requiring a close cardiological monitoring and long-term follow-up. This review aims at highlighting CAR-T cell-related cardiovascular complications and clarifying the pathogenetic mechanisms coming at play. Moreover, we will shed light on surveillance strategies and cardiotoxicity management protocols, as well as on future research perspectives in this expanding field.